2022
DOI: 10.1002/ctm2.822
|View full text |Cite
|
Sign up to set email alerts
|

The role of cell‐penetrating peptides in potential anti‐cancer therapy

Abstract: Due to the complex physiological structure, microenvironment and multiple physiological barriers, traditional anti‐cancer drugs are severely restricted from reaching the tumour site. Cell‐penetrating peptides (CPPs) are typically made up of 5–30 amino acids, and can be utilised as molecular transporters to facilitate the passage of therapeutic drugs across physiological barriers. Up to now, CPPs have widely been used in many anti‐cancer treatment strategies, serving as an excellent potential choice for oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 360 publications
0
42
0
1
Order By: Relevance
“…In this study, we found that the < 5 kDa CCP showed good anti-tumor activity. A lot of anti-tumor peptides have been found in recent years because of their advantages of targeting, specificity, safety, and so on ( 57 , 58 ). The anti-tumor mechanisms of these peptides are diversified: direct anti-tumor effect can be achieved by inhibiting the proliferation of tumor cells and promoting the apoptosis of tumor cells, or indirect anti-tumor effect can be achieved by enhancing and stimulating the immune response of the body to tumor cells, or by inhibiting the formation of tumor blood vessels ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the < 5 kDa CCP showed good anti-tumor activity. A lot of anti-tumor peptides have been found in recent years because of their advantages of targeting, specificity, safety, and so on ( 57 , 58 ). The anti-tumor mechanisms of these peptides are diversified: direct anti-tumor effect can be achieved by inhibiting the proliferation of tumor cells and promoting the apoptosis of tumor cells, or indirect anti-tumor effect can be achieved by enhancing and stimulating the immune response of the body to tumor cells, or by inhibiting the formation of tumor blood vessels ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that some CPPs lack tumor-specificity which could lead to drug delivery to cells in healthy tissues, there have been several attempts to enhance the specificity of CPPs-based delivery by taking advantage of the natural targeting abilities of antibodies and antigens [ 140 , 141 , 142 , 143 , 144 ]. For instance, by linking the antibody against tumorous cells’ highly expressed antigens to a CPP-siRNA complex, siRNA gene-drug delivery can be achieved with high levels of specificity and little cytotoxicity [ 145 ].…”
Section: Potential Diagnostics and Therapeuticsmentioning
confidence: 99%
“…Biocompatibility and maintenance of viability of normal cells are another aspect to consider in CPP-mediated delivery. On the other hand, if the target of the CPP-cargo is to reduce the proliferation of aberrant cells, such as cancer cells, the reduction of viability for those cells would be welcome (Zhou et al, 2022). Although some general online tools (Table 1) are available for predicting toxicity, or immunogenicity, allergenicity, the possible effects should be confirmed experimentally.…”
Section: Toxicity and Biocompatibility Of Cpp And Cpp-cargo In Vitro ...mentioning
confidence: 99%